2016
DOI: 10.3322/caac.21357
|View full text |Cite
|
Sign up to set email alerts
|

2016 US lymphoid malignancy statistics by World Health Organization subtypes

Abstract: Collectively, lymphoid neoplasms are the fourth most common cancer and the sixth leading cause of cancer death in the United States. The authors provide contemporary lymphoid neoplasm statistics by subtype based on the 2008 World Health Organization classifications, including the most current US incidence and survival data. Presented for the first time are estimates of the total numbers of US lymphoid neoplasm cases by subtype as well as a detailed evaluation of incidence and survival statistics. In 2016, 136,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
610
3
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 871 publications
(709 citation statements)
references
References 62 publications
17
610
3
16
Order By: Relevance
“…1 Despite its aggressive disease course,~50% to 70% of patients may be cured by current standard of care consisting of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy. 2 Nevertheless, R-CHOP is found to be inadequate in 30% to 40% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite its aggressive disease course,~50% to 70% of patients may be cured by current standard of care consisting of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy. 2 Nevertheless, R-CHOP is found to be inadequate in 30% to 40% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…About 4,292,000 new cases of cancer and 2,814,000 cancer-related deaths were estimated in China in 2015 [2]. It was reported that leukemia is the sixth leading cause of cancer death [3].…”
Section: Aimmentioning
confidence: 99%
“…About 4,292,000 new cases of cancer and 2,814,000 cancer-related deaths were estimated in China in 2015 [2]. It was reported that leukemia is the sixth leading cause of cancer death [3].Both genetic and environmental factors have been reported to cause of leukemia [4,5]. Combination of chemotherapy, radiation therapy and bone marrow transplant are involved in treatment of leukemia [6].…”
mentioning
confidence: 99%
“…Lymphoid neoplasms are reported to be the fourth most common malignancy in the US and the sixth leading cause of cancer-related deaths [1]. Extra-nodal lymphomas are seen most commonly in the skin, followed by stomach, oropharynx, and small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of gastrointestinal tract lymphomas are B-cell in origin and are found in the stomach, while only a small percentage are T-cell lymphomas and these are most commonly seen in the small bowel [2]. Enteropathy-associated T-cell lymphoma (EATL) is a rare entity with approximately 50 new cases reported in 2016 [1]. It is estimated that around 2–3% of patients with celiac disease (CD) develop an intestinal lymphoma, with 65% being of T-cell origin [3,4].…”
Section: Introductionmentioning
confidence: 99%